2003
DOI: 10.1007/bf02723163
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in BCG immunization

Abstract: Despite controversies BCG vaccination has stood the test of time. World Health Organization continues to recommend its use in infant immunization programme in countries with heavy endemicity and where threatening HIV epidemic in an emerging problem > 85% efficacy have been established in recent years against hematogenous spread of the disease and > or = 50% efficacy even against pulmonary tuberculosis. Host related factors, agent related factors, vaccine related factors and inadequacy of evaluation tests deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Although the efficacy of BCG in preventing active TB in adults has been challenged, it saves millions of lives by preventing severe, disseminated extra-pulmonary TB, including miliary and meningitis TB in young children (Parthasarathy, 2003). As the genome sequences of M.tb and M. bovis show over 99.95 % identity, and the pathological changes caused by M. bovis in cattle are also similar to those of human TB, M. bovis and its isogenic attenuated strain BCG are ideal model strains for studying M.tb pathogenesis and immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Although the efficacy of BCG in preventing active TB in adults has been challenged, it saves millions of lives by preventing severe, disseminated extra-pulmonary TB, including miliary and meningitis TB in young children (Parthasarathy, 2003). As the genome sequences of M.tb and M. bovis show over 99.95 % identity, and the pathological changes caused by M. bovis in cattle are also similar to those of human TB, M. bovis and its isogenic attenuated strain BCG are ideal model strains for studying M.tb pathogenesis and immunity.…”
Section: Introductionmentioning
confidence: 99%
“…These results agree with the reported BCG vaccine efficacy in protection against pulmonary TB, ranging 50-80 %. 22 A previous study by on 148 scar negative-BCG vaccinated-UK adolescents, showed increased in-vitro INF-γ production at 3 months (87 % responders) and 12 months (74 % responders) after BCG vaccination with the Danish strain. 23 In their study, INF-γ levels increased by 12.4 folds and 7.5 folds at 3 and 12 months respectively in comparison to non-vaccinated controls, with gradual reduction of response till 14 years post-vaccination.…”
Section: Discussionmentioning
confidence: 88%